2015
DOI: 10.1007/s11010-015-2534-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a bovine sperm acrosomal matrix protein and its mechanism of interaction with acrosomal hydrolases

Abstract: Fertilization, the union of male and female gametes to create offspring, is an intricate biological process dependent upon several biochemical and physiological events. Our understanding of the functions of protein constituents of the outer acrosomal membrane-associated matrix complex (OMC) is limited. A highly purified OMC fraction isolated from bovine cauda sperm heads is comprised of 54, 50, 45, and 38–19kDa polypeptides. The objective of this study is to identify and to characterize the 45kDa (OMC45) polyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
5
1
Order By: Relevance
“…Nagdas et al () recently identified a 45‐kDa acrosomal matrix protein, localized at the acrosomal cap of bovine epididymal spermatozoa, as TEKT3; however, we detected TEKT3 as a 55‐kDa protein residing at the post‐acrosomal region of bovine spermatozoa (Fig. ).…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Nagdas et al () recently identified a 45‐kDa acrosomal matrix protein, localized at the acrosomal cap of bovine epididymal spermatozoa, as TEKT3; however, we detected TEKT3 as a 55‐kDa protein residing at the post‐acrosomal region of bovine spermatozoa (Fig. ).…”
Section: Discussioncontrasting
confidence: 50%
“…The equatorial subsegment is also hypothesized to be a site where membrane fusion is initiated between sperm and egg at fertilization (Jones et al, 2008). Nagdas et al (2015) recently identified a 45-kDa acrosomal matrix protein, localized at the acrosomal cap of bovine epididymal spermatozoa, as TEKT3; however, we detected TEKT3 as a 55-kDa protein residing at the postacrosomal region of bovine spermatozoa (Fig. 1).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…These downregulated proteins make contact with each other to develop complex interacting networks, which widely participate in vesicle formation and transport, sperm head organisation, fertilisation, acrosome assembly and sperm axoneme assembly (figure 5C). According to the literature, nine of these proteins, including ZPBP1, SPACA1, SPINK2, CSNK2A2, DPY19L2, CCDC62, CCIN, TEKT2 and TEKT3, are explicitly related to the formation of the acrosome 17–24. Additionally, H1-7 is associated with spermatid nucleus differentiation25; SPAM126and ACR27 are involved with the binding of sperm to zona pellucida and TEKT5 participates in sperm flagella 28.…”
Section: Resultsmentioning
confidence: 99%
“…Because IVF bypasses all such interactions with the female reproductive tract, the results from IVF experiments do not cover all aspects of naturally occurring fertilization. Nonetheless, IVF is still a promising approach for discovering new molecular models for sperm-ZP interactions (Visconti and Florman 2010;Redgrove et al 2012;Nagdas et al 2015). A recent study using gene rescue experiments clearly demonstrated that human spermatozoa could recognize the human zona pellucida protein ZP2 (Avella et al 2014).…”
Section: Adhesion To the Zpmentioning
confidence: 99%